2023
DOI: 10.3390/mi14020254
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Performance Evaluation of Hemispherical Coriolis Vibratory Gyroscopes

Abstract: In this paper, the oscillation patterns and characteristics of gyroscopic reaction to rotation-induced Coriolis force and phase relations are reviewed by examining the main principles of operation of Coriolis vibratory gyroscopes based on the dynamic relations and proposed improvements in performance using parameter changes. Coriolis vibratory gyroscopes (CVGs) are among the most modern applicable gyroscopes in position detection that have replaced traditional gyroscopes due to some great features of the desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Gyroscopes are employed to determine either the rotation angle or angular velocity of objects. Gyroscopes find extensive applications in areas including platform stabilization, consumer products, automobiles, the aerospace industry, structural health monitoring and inertial navigation systems [1,2]. There are three main types of gyroscopes: Mechanical Gyroscopes [3], Optical Gyroscopes [4] and Coriolis Vibratory Gyroscopes (CVGs) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Gyroscopes are employed to determine either the rotation angle or angular velocity of objects. Gyroscopes find extensive applications in areas including platform stabilization, consumer products, automobiles, the aerospace industry, structural health monitoring and inertial navigation systems [1,2]. There are three main types of gyroscopes: Mechanical Gyroscopes [3], Optical Gyroscopes [4] and Coriolis Vibratory Gyroscopes (CVGs) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Gyroscopes are essential inertial sensors used to measure the rotation angle or angular velocity of an object and are critical components of inertial navigation systems. Traditional gyroscopes have been widely used in fields such as platform stability, aerospace, and inertial navigation [1][2][3][4] . Thanks to the progress in micromachining technology, chip-scale monolithic gyroscopes have been developed with features such as light weight, small size, and low power consumption, making them suitable for consumer electronics applications such as smartphones 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the piezoelectric effect, the input interdigital transducer (IDT) can generate an SAW that propagates along the surface of the piezoelectric substrate, which can then be converted back into an electrical signal by the output IDT [17,18]. When the SAW propagates, the Coriolis force generated by the rotation of the SAW angular velocity sensor acts on the vibrating particles [19] and generates a secondary pseudo-SAW, coupled with the original SAW [20], leading to changes in the phase velocity of the SAW, a process known as the SAW gyroscopic effect [21]. On the basis of this, in this paper, the dual delay line angular velocity sensor with distributed metal dot array is taken as the research object, the structure of which is shown in Figure 1, and which is composed of IDTs, metal dot arrays, and a layered substrate.…”
Section: Introductionmentioning
confidence: 99%